Insubordination to Unlawful Order: Praktek di Antara Bangsa-Bangsa dan Tantangan Penerapannya di Indonesia - Mochammad Arief Agus; Alif Imam Dzaki (Jurnal Hukum Lex Generalis, 2023)
The momentum of the cases of Ferdy Sambo, Kanjuruhan, and the Santa Cruz incident in the past has raised legal awareness that orders from superiors can cause subordinates to act against the law. Can subordinates refuse orders from superiors that are against the law? What are the legal consequences that they must bear? Does the law even require them to refuse such orders to prevent the law from being violated? Is there a concept that governs this in international law? The method used is a normative legal study and is sharpened by discussing special cases from the practice of nations. Discussions related to the topic of Insubordination to Unlawful Order in history, provisions of international law, state practice, and Indonesian positive law as well as the main challenges that will be faced. It ends with the conclusion that countries have maintained this concept well even though there are differences in implementation, while Indonesia has not implemented it in the national legal system and will cause various legal problems. It is highly recommended that Indonesia adopt this concept as a response to the increasing intensity of global conflicts in the future.